Lwandle : criminalisation of a community - Sloth-Nielsen, Julia (Institute of Criminology, 2023)
This work tells the history of the current crisis facing the community of Lwandle, "the hostel by the sea" near Strand and Somerset West in the Western Cape. Despite all the media propaganda about consultation with "recognised and moderate leaders", despite government promises that legislation curtailing the free movement of blacks would be abolished, despite the State President's undertaking that apartheid would go, yet the people who live in this settlement have little hope of being able to remain there with their families for much longer. I will attempt to illustrate the socio-economic conditions which prevail in their community, to detail the background to the current stage in their struggle to promote family life at Lwandle and to place this in a broader perspective to state policy and apartheid reform in late 198 7. Accordingly, Chapter 1 will look at the history of Lwandle hostel, the geographic environment, the demographic composition of the community and the social composition and community organisation that pertains there at present. Much of the information in this section was gleaned from my involvement with the community of Lwandle as the chairwoman of the local branch of the Black Sash and from my recurring meetings with sections of the community in order to try and resolve the question of their impending removal to another area (or, more recently, the removal of part of the community). Some information, too, emanates from an investigation by the Urban Foundation, conducted in 198 7, into the feasibility of providing suitable family housing at Lwandle. During the preparation of this report, I did, however, liase a great deal with the 'research team who compiled it, and (hopefully) succeeded in imparting some of the information now embodied in the report. In Chapter 2 a summary of legal developments relating to the abolition of influx control will be provided, and other enactments controlling the movement of peoples throughout South Africa examined. In this regard current government policy and stated objectives pertaining to both influx control and housing (with particular attention to single sex hostel accommodation) must be included in order to provide a basis for analysis in the final Chapter, Chapter 4. Chapter 3 will focus on the arrest in May 1986 of 1.58 women at Lwandle hostel on charges amounting to trespass. The involvement of the local branch of the Black Sash in the future of the Lwandle community was a reaction to the immediate need of those women who were arrested. Some specific case studies were completed, and these will be discussed in this Chapter. Further police action in Lwandle after May 1986 will, insofar as such details are known to me, also be mentioned. Finally, in Chapter 4 the problematic position in which the residents of Lwandle now find themselves will be outlined, and certain conclusions about the general political scenario that obtains at present in South Africa (with reference to criminological issues) will be drawn.